Penyuluhan tentang Pemanfaatan Fasilitas Kesehatan sebagai Sarana Pengobatan pada Penderita Hipertensi Di Desa Taipanggabe Wayu Matantimali Sulawesi Tengah - Hasinuddin, Mutmainnah Hasi; Restawan, I Gede; Purwiningsih, Sri; Kantohe, Imelda; Sabarulin, Sabarulin; Alfira, Anggri; Assa, Yunita; Sepang, Janice; Susanto, Denny; Kose, Dwi Beni (Jurnal Abdimas Kesehatan (JAK), 2024)
Hypertension is a non-communicable disease (NCD) which is a health problem in society, one of ten diseases that cause mortality in Asia (Saha, Sana, Shana, 2006). Hypertension can cause coronary heart disease, congestive heart failure, stroke, kidney failure. 70% of strokes can be fatal and 65% affect the kidneys. This phenomenon is caused by changes in people's lifestyles globally, such as the easier it is to get ready-to-eat food, the lower consumption of salt, fat, sugar and calories. which continues to increase so that it has a big role in increasing the incidence of hypertension and the prevalence of hypertension continues to increase throughout the world in adults, 29.2%. There are 8 provinces in Indonesia with cases of hypertension sufferers exceeding the average, namely: South Sulawesi (27%), West Sumatra (27%), West Java (26%), West Java (26%), East Java (25%), North Sumatra (24%), South Sumatra (24%), Central Sulawesi (29.8%) Based on the 2020 Central Sulawesi Health Profile, the estimate for hypertension sufferers aged ≥ 15 years in Central Sulawesi province is 384,072 (2.33%). In the villages of Taipanggabe, Wayu and Matantimali, Sigi Regency, Central Sulawesi Province, 17 elderly people were found to have hypertension.